2009
DOI: 10.1038/sj.bjc.6604887
|View full text |Cite
|
Sign up to set email alerts
|

RASSF1A hypermethylation in pretreatment serum DNA of neuroblastoma patients: a prognostic marker

Abstract: The tumour suppressor gene RASSF1A is known to be frequently silenced by promoter hypermethylation in neuroblastoma tumours. Here we explored the possible prognostic significance of aberrant promoter hypermethylation of RASSF1A in serum DNA samples of patients with neuroblastoma as a surrogate marker for circulating tumour cells. We analysed the methylation status of the RASSF1A gene in matched tumour and pretreatment serum DNA obtained from 68 neuroblastoma patients. Hypermethylation of RASSF1A in tumour samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…Previous studies have reported hypermethylation of the 5′ CpG island of RASSF1A in all xenografts, most cell lines and primary tumors tested, suggesting that DNA methylation is likely a critical mechanism in inactivation of the RASSF1A gene (Lo et al, 2001;Misawa et al, 2009;Kwong et al, 2002;Puente et al, 2008). Methylation affects gene expression either directly by interfering with binding of transcription factors and/or indirectly by recruiting histone deacetylases, leading to gene inactivation.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have reported hypermethylation of the 5′ CpG island of RASSF1A in all xenografts, most cell lines and primary tumors tested, suggesting that DNA methylation is likely a critical mechanism in inactivation of the RASSF1A gene (Lo et al, 2001;Misawa et al, 2009;Kwong et al, 2002;Puente et al, 2008). Methylation affects gene expression either directly by interfering with binding of transcription factors and/or indirectly by recruiting histone deacetylases, leading to gene inactivation.…”
Section: Discussionmentioning
confidence: 95%
“…For these cases, aberrant hypermethylation of the DCR2 promoter of the serum DNA has been helpful in predicting prognosis, therapeutic efficacy, and detecting reoccurrence in (non MNA) neuroblastomas. Also, determination of the hypermethylation status of RASSF1A of serum DNA is another prognostic marker for the outcome in neuroblatoma patients [94–96]. …”
Section: Neoplasmsmentioning
confidence: 99%
“…Similarly, methylation patterns in RASSF1 and CASP8 have been reported to be correlated, although the clinical significance of this association is yet to be established (Astuti et al, 2001;Lazcoz et al, 2006). More recently, a study examining the level of promoter hypermethylation of RASSF1 in serum DNA samples of patients with neuroblastoma found increased levels of RASSF1 hypermethylation associated with older age, stage 4 disease, and MYCN amplification (Misawa et al, 2009). These promising findings indicate that screening for methylation status of RASSF1 and other genes in patient serum at diagnosis may be further developed for use as a non-surgical prognostic predictor of neuroblastoma outcome.…”
Section: Tumor Suppressor Genesmentioning
confidence: 99%